Quality of life in relation to the traffic pollution indicators NO2 and NOx: results from the Swedish GA2LEN survey. Issue 1 (17th August 2014) - Sommar, Johan Nilsson; Ek, Alexandra; Middelveld, Roelinde; Bjerg, Anders; Dahlén, Sven-Erik; Janson, Christer; Forsberg, Bertil
Abstract : Background: Asthma is a chronic disease that may affect daily activities and quality of life. Asthmatics have higher incidence of chronic rhinosinusitis (CRS) and asthma is associated with sinonasal inflammation and nasal symptoms, that all impair quality of life. Worsening of asthma has been found associated with levels of nitrogen dioxide as traffic indicator. Aims: The aim of the study was to evaluate the impact of traffic pollution indicated by nitrogen oxides (NO2 and NOx ) on quality of life in asthmatic persons, individuals with CRS and controls. Methods: Within the Swedish Ga 2 len (Global Allergy and Asthma European Network), 605 asthmatics with and without CRS, 110 individuals with CRS only and 226 controls from four cities were surveyed. The mini Asthma Quality of life Questionnaire (mAQLQ) and the Euro Quality of Life (EQ-5D) health questionnaire were used. Air pollution concentrations at the home address were modelled using dispersion models. Results: Levels of NO2 (geometric mean 10.1 μg/m 3 (95% CI 9.80 to 10.5) and NOx (12.1 μg/m 3, 11.7 to 12.6) were similar among conditions (controls, asthmatics, individuals with CRS and asthmatics with CRS). The mAQLQ overall score was not found associated with levels of NO2 or NOx, with or without adjustments, and neither was scores within each of the four domains of mAQLQ: symptoms, activity limitations, emotional functions and effects of environmental stimuli. The mean EQ-5D index value, based on the five dimensions mobility, self-care, usual activities, pain/discomfort and anxiety depression, was also found unrelated to NO2 and NOx . Conclusions: At moderate exposure levels traffic pollution appears not to affect quality of life.